Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1080/00994480.2004.10748423
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Surface Luminances in Offices, by Evolution

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
(24 reference statements)
1
27
0
Order By: Relevance
“…He highlighted that the same findings were found in both experiments. Similarly, Newsham et al 17,19 highlighted the consistency found between the optimal luminous environments obtained for each observer of a panel of 40 observers, who judged the CGI of an office room on a computer, and data collected from a real-world test in which observers adjust lighting according to their preferences. However, virtual environment tests have limits, 18 especially when used for experiments about glare or colour rendering.…”
Section: Introductionmentioning
confidence: 97%
“…He highlighted that the same findings were found in both experiments. Similarly, Newsham et al 17,19 highlighted the consistency found between the optimal luminous environments obtained for each observer of a panel of 40 observers, who judged the CGI of an office room on a computer, and data collected from a real-world test in which observers adjust lighting according to their preferences. However, virtual environment tests have limits, 18 especially when used for experiments about glare or colour rendering.…”
Section: Introductionmentioning
confidence: 97%
“…Flynn introduced the use of semantic differential scales to gather subjective assessments of daylight quality in terms of visual clarity, spaciousness, evaluation, relaxation, social prominence, complexity, modifying influence, and spatial modifiers 8 . Numerous studies thereafter have employed the use of these scales to conduct daylight quality research in real spaces and simulated or photographed views 10,30,40,41 . For the proposed study, the authors have focused on bi-polar semantic differential scales associated with complexity and spatial modifiers as well as visual interest.…”
Section: Methodsmentioning
confidence: 99%
“…To conduct qualitative lighting research using digital images, existing studies have applied subjective rating methods to measure impressions of lighting composition in HDR photographs 11,[30][31][32] as well as rendered images of a simulated office environment 10 . These experiments have asked participants to view a series of images and then respond to semantic differential ratings 8 for pleasantness, contrast, brightness, spaciousness, and/or distribution, which were then compared to photometric measurements taken from the digital images.…”
Section: Existing Experimental Studiesmentioning
confidence: 99%
“…To evaluate the visual impacts of luminosity within interior architecture, existing research has relied on average luminance or "brightness," threshold luminance, and luminance variation (or standard deviation) in line with occupant surveys to establish trends in preference. Survey-based studies most commonly rely on high-dynamic-range HDR images, digital photographs or renderings produced through Radiance, which provide an expanded range of photometric information, allowing us to evaluate characteristics such as brightness and contrast [19,20]. Some studies have found that both mean luminance and luminance variation within an office environment contribute to occupant preference [21], whereas others have discovered that luminance distribution across an occupant's field-of-view [22] as well as the strength of variation are factors of preference [23].…”
Section: Perceptual Daylight Metricsmentioning
confidence: 99%